Mechanism of Spin-Orbit Effects on the Ligand NMR Chemical Shift in Transition-Metal Complexes: Linking NMR to EPR - Vícha, Jan; Straka, Michal; Munzarová, Markéta L; Marek, Radek (Journal of chemical theory and computation, 2014)
Relativistic effects play an essential role in understanding the nuclear magnetic resonance (NMR) chemical shifts in heavy-atom compounds. Particularly interesting from the chemical point of view are the relativistic effects due to heavy atom (HA) on the NMR chemical shifts of the nearby light atoms (LA), referred to as the HALA effects. The effect of Spin-Orbit (SO) interaction originating from HA on the nuclear magnetic shielding at a neighboring LA, σ(SO), is explored here in detail for a series of d(6) complexes of iridium. Unlike the previous findings, the trends in σ(SO) observed in this study can be fully explained neither in terms of the s-character of the HA-LA bonding nor by trends in the energy differences between occupied and virtual molecular orbitals (MOs). Rather, the σ(SO) contribution to the total NMR shielding is found to be modulated by the d-orbital participation of the heavy atom (Ir) in the occupied and virtual spin-orbit active MOs, i.e., those which contribute significantly to the σ(SO). The correlation between the d-character of σ(SO)-active MOs and the size of the corresponding SO contribution to the nuclear magnetic shielding constant at LA is so tight that the magnitude of σ(SO) can be predicted in a given class of compounds on the basis of d-orbital character of relevant MO with relative error smaller than 15%. This correspondence is supported by an analogy between the perturbation theory expressions for the spin-orbit induced NMR σ-tensor and those for the EPR g-tensor as well as the A-tensor of the ligand. This correlation is demonstrated on a series of d(5) complexes of iridium. Thus, known qualitative relationships between electronic structure and EPR parameters can be newly applied to reproduce, predict, and understand the SO-induced contributions to NMR shielding constants of light atoms in heavy-atom compounds.